Promotif kesehatan melalui edukasi Keluarga Berencana (KB) - Sitti Fatimah; Musni Musni; Desi Heriyana (JOURNAL of Public Health Concerns, 2026)
Background: Family planning (FP) is an effort undertaken by married couples to regulate the number, spacing, and timing of their children through the use of contraceptive methods to create a healthy, prosperous, and quality family. According to the World Health Organization (WHO), family planning is an action that enables individuals and couples to anticipate and achieve the desired number of children and determine the spacing and timing of births through the use of safe and effective contraceptive methods. The Family Planning (FP) program is not merely an effort to regulate the number of children, but rather a preventive health strategy proven to reduce maternal and infant mortality, improve the quality of family life, and support sustainable development. Family planning education shifts the societal paradigm from "many children, much fortune" to "fewer children, healthy, and prosperous." This is an effective promotive-preventive effort to improve maternal and child health, particularly in rural areas such as Palongki Village. Purpose: To increase public knowledge about family planning (FP). Method: This community service activity was held on Sunday, February 1, 2026, at 10:00 a.m. WITA (Central Indonesian Time) at the Palongki Village Office. The primary goal was to optimize knowledge about family planning among couples of childbearing age and pregnant women. Thirty-eight respondents, supported by village officials and local health workers, participated in the activity. The activity employed an educational, counseling, and participatory approach, employing a one-group pre-test and post-test design. The educational materials were based on the guidelines of the National Population and Family Planning Board (BKKBN) and the Ministry of Health of the Republic of Indonesia, and adapted to the local context. The materials were delivered through interactive lectures. Evaluation was conducted by analyzing the pre-test and post-test results, calculating the difference in the respondents' average knowledge scores and presenting them descriptively to assess changes in their knowledge levels after the educational activity. Results: The average age of respondents was 31.87 years with a standard deviation of ±6.53 years. The majority of respondents were in the 20-30 age range (50.0%). The majority of respondents (84.2%) accepted family planning (FP), and the majority (84.2%) also believed that education about family planning was very beneficial. Furthermore, the level of knowledge of respondents about family planning before the educational activity was 5 (13.2%) in the good category, 10 (26.3%) in the adequate category, and 23 (60.5%) in the poor category. Meanwhile, the level of knowledge of respondents after the educational activity was 30 (78.9%) in the good category and 8 (21.1%) in the adequate category. Conclusion: The educational intervention activity was proven effective in increasing mothers' knowledge about family planning (FP) and encouraging positive changes in attitudes and behaviors regarding contraceptive choice. Increasing mothers' knowledge also directly contributes to improving public health through pregnancy planning and appropriate birth spacing. Suggestion: Integrated Health Posts (Posyandu) are expected to conduct regular monitoring and actively empower cadres to provide knowledge about family planning, so that programs can be effectively implemented in the wider community. Keywords: Contraception; Couples of reproductive age; Family planning; Health education; Reproductive health Pendahuluan: Keluarga berencana (KB) adalah upaya yang dilakukan oleh pasangan suami istri untuk mengatur jumlah anak, jarak kelahiran, dan waktu kelahiran melalui penggunaan metode kontrasepsi guna mewujudkan keluarga yang sehat, sejahtera, dan berkualitas. Menurut World Health Organization (WHO), family planning adalah tindakan yang memungkinkan individu dan pasangan untuk mengantisipasi dan mencapai jumlah anak yang diinginkan serta menentukan jarak dan waktu kelahiran melalui penggunaan metode kontrasepsi yang aman dan efektif. Program Keluarga Berencana (KB) bukan hanya sekedar upaya pengaturan jumlah anak, melainkan strategi kesehatan preventif yang terbukti menurunkan angka kematian ibu dan bayi, meningkatkan kualitas hidup keluarga serta mendukung pembangunan berkelanjutan. Edukasi KB mengubah paradigma masyarakat dari “banyak anak banyak rezeki” menjadi “sedikit anak, sehat, dan sejahtera”. Ini adalah upaya promotif–preventif yang efektif untuk meningkatkan derajat kesehatan ibu dan anak, khususnya didaerah pedesaan seperti Desa Palongki. Tujuan: Untuk meningkatkan pengetahuan tentang keluarga berencana (KB) pada masyarakat. Metode: Kegiatan pengabdian kepada masyarakat ini dilaksanakan pada hari Minggu 1 Februari 2026, pukul 10.00 WITA di Kantor Desa Palongki. Dengan sasaran utama adalah optimalisasi pengetahuan tentang keluarga berencana pada pasangan usia subur dan ibu hamil. Melibatkan 38 responden dan dukungan perangkat desa dan kader kesehatan setempat. Kegiatan dilakukan dengan pendekatan edukatif, konseling, dan partisipatif, menggunakan pre-test dan post-test one group design. Materi edukasi berdasarkan pedoman BKKBN dan Kementerian Kesehatan Republik Indonesia, serta disesuaikan dengan konteks lokal. Materi disampaikan melalui ceramah interaktif. Evaluasi dilakukan dengan menganalisa hasil pre-test dan post-test yaitu menghitung selisih nilai rata-rata pengetahuan responden dan disampaikan secara deskriptif untuk melihat perubahan tingkat pengetahuan responden setelah kegiatan edukasi. Hasil: Menunjukkan bahwa rata-rata usia responden adalah 31.87 tahun dengan standar deviasi ±6.53 tahun dan mayoritas responden berada di rentang usia 20-30 tahun yaitu sebesar 50.0%. Sebagian besar responden merupakan akseptor KB yaitu sebesar 84.2% dan sebagian besar juga responden berpendapat bahwa edukasi tentang KB sangat bermanfaat yaitu sebesar 84.2%. Sedangkan tingkat pengetahuan responden tentang KB sebelum kegiatan edukasi adalah sebanyak 5 (13.2%) dalam kategori baik, sebanyak 10 (26.3%) dalam kategori cukup dan sebanyak 23 (60.5%) dalam kategori kurang. Sedangkan tingkat pengetahuan responden setelah kegiatan edukasi menjadi sebanyak 30 (78.9%) dalam kategori baik dan sebanyak 8 (21.1%) dalam kategori cukup. Simpulan: Kegiatan intervensi edukasi terbukti efektif meningkatkan pengetahuan ibu tentang Keluarga Berencana (KB) serta mendorong perubahan positif pada sikap dan perilaku pemilihan alat kontrasepsi. Peningkatan pengetahuan ibu tentang juga berkontribusi langsung dalam menciptakan kesehatan masyarakat melalui perencanaan kehamilan dan mengatur jarak kelahiran dengan tepat. Saran: Diharapkan kepada Posyandu untuk melakukan pemantauan secara rutin dan secara aktif memberdayakan kader dalam memberikan pengetahuan tentang KB, agar penerapan program-program dapat dilaksanakan dengan baik di masyarakat yang lebih luas.